2010
DOI: 10.2174/1874372201004010095
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Psoriasis - A Forgotten Entity?~!2010-04-15~!2010-07-06~!2010-08-06~!

Abstract: Follicular psoriasis is a common yet under reported entity. Major dermatology textbooks fail to emphasise and even neglect this important diagnosis and since its original description in 1920 there have been only three reports in the published literature. As a result the diagnosis is seldom entertained by dermatology trainees in the differential diagnosis of a folliculocentric skin disease. We present a case of follicular psoriasis which was initially mis-diagnosed as lichen planopilaris and summarise the key f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…This patient had no previous diagnosis of psoriasis and lacked the classical findings for psoriasis vulgaris. Thomas et al presented a case in an 18year-old Asian male who exhibited bilateral follicular lesions involving the thighs, calves, and arms, initially misinterpreted as lichen planopilaris [9]. Patil et al described a 13-year-old boy with symptomatic scaling and erythema of the skin that began as horny papules on the knees and elbows that evolved into erythematous scaly papules encompassing the entire body [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This patient had no previous diagnosis of psoriasis and lacked the classical findings for psoriasis vulgaris. Thomas et al presented a case in an 18year-old Asian male who exhibited bilateral follicular lesions involving the thighs, calves, and arms, initially misinterpreted as lichen planopilaris [9]. Patil et al described a 13-year-old boy with symptomatic scaling and erythema of the skin that began as horny papules on the knees and elbows that evolved into erythematous scaly papules encompassing the entire body [10].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentations and microscopic examinations in the previously described reports were similar to the findings in our cases. A summary of these 25 cases is presented in Table 1 [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Keratin 17 (K17) is a structural protein found in basal cells of various complex epithelial tissues like nails, hair follicles, sebaceous glands, and eccrine sweat glands. Thomas et al [13] (2010), UK Recently, it has gained attention in psoriasis research as studies have shown its abnormal expression in suprabasal layers of keratinocytes in psoriatic lesions as compared to normal skin. Cytokines (including IL-17A and IL-22) which are associated with the Th17 and IL-22-producing CD4+ T cells, can increase K17 expression in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Since this initial publication, occasional additional cases of FP have been reported. [2][3][4][5][6][7][8][9][10][11] The current literature emphasizes the distinction of this condition from the cutaneous manifestation of classical psoriasis variants and stresses diagnostic difficulty due to its apparent rarity and relatively unfamiliar clinical presentation. This study aims to analyze the clinical, histological, and dermatoscopic findings as well as treatment options of all FP cases reported in the literature.…”
Section: Introductionmentioning
confidence: 99%